(untitled) (New Jersey, 2005)
Parallel Metaheuristics brings together an international group of experts in parallelism and metaheuristics to provide a much-needed synthesis of these two fields. Readers discover how metaheuristic techniques can provide useful and practical solutions for a wide range of problems and application domains, with an emphasis on the fields of telecommunications and bioinformatics. This volume fills a long-existing gap, allowing researchers and practitioners to develop efficient metaheuristic algorithms to find solutions.
Keywords: Mathematical optimization,Parallel algorithms,Operations,Toán học tối ưu,Thuật toán song song,Phép tính